Antimicrobial Photodynamic Therapy against Endodontic Enterococcus faecalis and Candida albicans Mono and Mixed Biofilms in the Presence of Photosensitizers: A Comparative Study with Classical Endodontic Irrigants - Diogo, Patrícia; Fernandes, Chantal; Caramelo, Francisco; Mota, Marta; Miranda, Isabel M.; Faustino, M. A. F.; Neves, M. G. P. M. S.; Uliana, Marciana P.; de Oliveira, Kleber T.; Santos, João M.; Gonçalves, Teresa (Frontiers in Microbiology, 2017)
Endodontic biofilms eradication from the infected root canal system remains as the primary focus in endodontic field. In this study it was assessed the efficacy of antimicrobial Photodynamic Therapy (aPDT) with the Zn(II)chlorin e6 methyl ester (Zn(II)e6Me) activated by red light against monospecies and mixed biofilms of Enterococcus faecalis and Candida albicans. The results were compared with the ones obtained with Rose Bengal (RB), Toluidine Blue-O (TBO), the synthetic tetracationic porphyrin (TMPyP) as well as classical endodontic irrigants (3% NaOCl, 17% EDTA and 2% CHX). The antimicrobial efficacy of aPDT towards monospecies and mixed biofilms was quantified resorting to safranin red method. The changes of biofilm organization and of cellular ultrastructure were evaluated through several microscopy techniques (light, laser confocal and transmission electron microscopy). Zn(II)e6Me once activated with light for 60 or 90 s was able to remove around 60% of the biofilm’s biomass. It was more efficient than TBO and RB and showed similar efficiency to TMPyP and classical irrigants, CHX and EDTA. As desirable in a PS, Zn(II)e6Me in the dark showed smaller activity than TMPyP. Only NaOCl revealed higher efficiency, with 70-90% of the biofilm’s biomass removal. The organization of biofilms and the normal microbial cell ultrastructure were extensively damaged by the presence of Zn(II)e6Me. aPDT with Zn(II)e6Me showed to be an efficient antimicrobial strategy deserving further studies leading to a future clinical usage in endodontic disinfection.